Introduction: Five Steps Toward a Religion–Ai Dialogue - Vestrucci, Andrea (Zygon, 2022)
This introduction to the thematic section of Zygon: Journal of Religion and Science on “Artificial Intelligence and Religion: Recent Advances and Future Directions” outlines the five articles by dividing them into two groups: the three that analyze the impact of recent advances in subsymbolic artificial intelligence (AI) on religion and theology, and the two that explore theological concepts in symbolic AI environments. These five articles are five steps toward a strong, deep, and interdisciplinary dialogue between the research in religion and the research in AI.